Physicochemical, Functional, and Macromolecular Properties of Waxy Yam Starches Discovered from Mapuey (Dioscorea trifida) Genotypes in the Venezuelan Amazon - Pérez, E.; Gibert, Olivier; Rolland Sabaté, Agnès; Jiménez, Y.; Sánchez, T.; Giraldo, A.; Pontoire, B; Guilois, S; Lahon, MC; Reynes, M; Dufour, D.L. (American Chemical Society, 2010)
Mapuey tubers in Venezuela are staple food for indigenous peoples from the Caribbean coast and Amazon regions. Noticeable differences between genotypes of yam starches were observed. Granules were large, triangular, or shell-shaped with monomodal particle size distribution between 24.5 and 35.5 ?m. Differential scanning calorimetry (DSC) analyses revealed onset gelatinization temperatures from 69.1 to 73.4 °C with high gelatinization enthalpy changes from 22.4 to 25.3 J g?1. All X-ray diffractograms of starches exhibit B-type crystallinity. Crystallinity degrees varied from 24% to 40%. The highest crystallinity was found for the genotype having the highest amylose content. Iodo-colorimetric, amperometric, and DSC amylose determinations varied from 1.4 to 8.7%, 2.2 to 5.9%, and 1.4 to 3.5% for Amazonian genotypes, in comparison with commercial Mapuey starches: 12.0, 9.5, and 8.7%, respectively. Solubility and swelling power at 90 °C varied from 2.1 to 4.4% and 20.5 to 37.0%, respectively. Gel clarity fluctuated from 22.4 to 79.2%, and high rapid visco analyzer (RVA) viscosity was developed at 5% starch suspension (between 1430 and 2250 cP). Amylopectin weight average molar mass M?w, radius of gyration RG, hydrodynamic coefficient ?G, and apparent molecular density dGapp were determined using high-performance size exclusion chromatography (HPSEC) and asymmetrical flow field flow fractionation (A4F) techniques coupled with multiangle laser light scattering (MALLS) on the Dioscorea trifida genotypes exhibiting the lowest and highest amylose contents. Amylopectins showed very similar molecular conformations. M?w values were 1.15 × 108 and 9.06 × 107 g mol?1 using HPSEC and A4F, respectively, thus, 3?5 times lower than those reported with the same techniques for other yam species, and very close to those of potato and cassava amylopectins. This discovery of a new natural amylose-free starch in the neglected yam Mapuey could present some potential for the food industry.